Interactions of multiple gene alterations in colorectal liver metastases - Kawaguchi, Yoshikuni; Velasco, Jenilette D.; Arvide, Elsa M.; Wei, Steven H.; Vauthey, Jean-Nicolas (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
The advancements in next generation sequencing have expanded the information available in clinical practice. Alterations of TP53, APC, RAS, PIK3CA, and SMAD4 are present in more than 10% of patients with colorectal liver metastases (CLM). Of these genes, TP53, RAS and SMAD4 were associated with worse survival in patients undergoing CLM resection. Testing multiple gene alterations provides a more precise prognosis for patients undergoing CLM resection and may be useful for better clinical decision making